2002
DOI: 10.1074/jbc.m202715200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Peptide Toxins That Block Mechanosensitive Ion Channels

Abstract: Mechanosensitive channels (MSCs) play key roles in sensory processing and have been implicated as primary transducers for a variety of cellular responses ranging from osmosensing to gene expression. This paper presents the first structures of any kind known to interact specifically with MSCs. GsMTx-4 and GsMtx-2 are inhibitor cysteine knot peptides isolated from venom of the tarantula, Grammostola spatulata (Suchyna, T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 50 publications
0
75
0
Order By: Relevance
“…This mode of action is similar to that reported for the insect-selective neurotoxin -HXTX-Hv1c, from the venom of the hexathelid spider H. versuta, that also inhibits BK Ca channels (Gunning et al, 2008). Homology modeling of -TRTX-Ec2 toxins on the known structure of -TRTX-Gr2a (formerly GsMTx-2, Oswald et al, 2002;Protein Data Bank ID 1LUP), revealed several pairs of basic and aromatic residues that could satisfy the requirements of a functional dyad (Fig. 8).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This mode of action is similar to that reported for the insect-selective neurotoxin -HXTX-Hv1c, from the venom of the hexathelid spider H. versuta, that also inhibits BK Ca channels (Gunning et al, 2008). Homology modeling of -TRTX-Ec2 toxins on the known structure of -TRTX-Gr2a (formerly GsMTx-2, Oswald et al, 2002;Protein Data Bank ID 1LUP), revealed several pairs of basic and aromatic residues that could satisfy the requirements of a functional dyad (Fig. 8).…”
Section: Discussionmentioning
confidence: 54%
“…Percentage identity (%I) is relative to -TRTX-Ec2a, whereas percentage homology (%H) includes conservatively substituted residues. The disulfide bonding pattern for the strictly conserved cysteine residues determined for -TRTX-Gr2a (Oswald et al, 2002) and -TRTX-Ps2a (Diochot et al, 1999) is indicated above the sequences; it is assumed that the -TRTX-Ec2 toxins share the same disulfide bonding pattern. The known mammalian targets (unless otherwise indicated) of these spider toxins are identified on the right, with channels identified in brackets indicating only weak affinity.…”
Section: Resultsmentioning
confidence: 99%
“…GsMTx4 follows the Inhibitory Cysteine Knot (ICK) motif with six cysteines (Pallaghy et al, 1994;Oswald et al, 2002), and as with similar neuroactive peptides, it is amphipathic ( Figure 5). The hydrophobic face is in green and the charged residues in red (negative) and blue (positive).…”
Section: Structurementioning
confidence: 99%
“…Using this sequence, we chemically synthesized GsMTx4 with a phenylalanine-amide at the C-terminal and determined the conditions for folding (Ostrow et al, 2003;Oswald et al, 2002). The synthetic peptide appeared indistinguishable from wild type peptide in all physicalchemical properties.…”
Section: Gsmtx4 a Peptide Blocker Of Sacs Isolation And Purificationmentioning
confidence: 99%
“…The following drugs were used (source): BQ123 (Calbiochem or Sigma), candesartan or CV11974 (generous gift of AstraZeneca, Mölndal, Sweden), cariporide or HOE642 (generous gift of Aventis Pharma, Frankfurt, Germany), GF203109X (Calbiochem), GsMtx-4 (prepared as described before (Ostrow et al, 2003;Oswald et al, 2002)), KB-R7943 (Tocris), L-NAME (Sigma), ML-7 (Calbiochem), PD145065 (Sigma), streptomycin (Sigma), wortmannin (Calbiochem).…”
Section: Drugsmentioning
confidence: 99%